Epidemiological study on gender bias and low-value practices in primary care: a study protocol - José Joaquín Mira; Irene Carrillo; Vicente F Gil-Guillen; Susanna Tella; Mercedes Guilabert; Maria Asunción Vicente; César Fernández; Elisa Chilet-Rosell; Concepcion Carratala-Munuera; Adriana Lopez-Pineda; Virtudes Pérez-Jover; Domingo Orozco-Bletrán; et al. (BMJ Open, 2023)
Introduction Evidence shows that gender has a substantial impact on health behaviours, access to and use of health systems and health system responses. This study aims to assess gender bias in patients subjected to low-value practices in the primary care setting and to develop recommendations for reducing adverse events that women experience for this reason.Methods and analysis A Delphi study will be performed to reach a consensus on the ‘Do Not Do’ recommendations with a possible gender bias. A retrospective cohort study in a random selection of medical records will then be carried out to identify the frequency of adverse events that occur when the selected ‘Do Not Do’ recommendations are ignored. Qualitative research techniques (consensus conference and nominal group) will be carried out to develop recommendations to address any gender bias detected, considering barriers and facilitators in clinical practice.Ethics and dissemination The study was approved by the ethics committee of San Juan de Alicante Hospital (San Juan de Alicante, Spain) Reference N. 21/061. We will disseminate the research findings via peer-reviewed articles, presentations at national and international scientific forums and webinars.Trial registration number The study was registered at ClinicalTrials.gov (NCT05233852) on 10 February 2022.